Why primatology needs local knowledge - Sam Adue; Walter Akankwasa; Jackson Asua; Gideon Atyo; Bosco Chandia; Noémie Freymond; Vicent Kizza; Harmonie Klein; Monday M’Botella; Stephen Mugisha; Geresomu Muhumuza; Mike Matthew Musiimenta; et al. (Primates, 2026)

Dead-infant carrying by chimpanzee mothers in the Budongo Forest - Adrian Soldati; Pawel Fedurek; Catherine Crockford; Sam Adue; John Walter Akankwasa; Caroline Asiimwe; Jackson Asua; Gideon Atayo; Boscou Chandia; Elodie Freymann; Caroline Fryns; Geresomu Muhumuza; et al. (Primates, 2022)
It has been suggested that non-human primates can respond to deceased conspecifics in ways that suggest they experience psychological states not unlike humans, some of which could indicate they exhibit a notion of death. Here, we report long-term demographic data from two East African chimpanzee groups. During a combined 40-year observation period, we recorded 191 births of which 68 died in infancy, mostly within the first year. We documented the post-mortem behaviour of the mothers and describe nine occasions where Budongo chimpanzee mothers carried infants for 1–3 days after their death, usually until the body started to decompose. We also observed three additional cases of extended carrying lasting for more than 2 weeks, one of which was followed by the unusual extended carrying of an object and another which lasted 3 months. In each case, the corpses mummified. In addition, we report four instances of recurring dead-infant carrying by mothers, three of whom carried the corpse for longer during the second instance. We discuss these observations in view of functional hypotheses of dead-infant carrying in primates and the potential proximate mechanisms involved in this behaviour.